PERBEDAAN VEGETATIF DUA JENIS EKONOMI ETLINGERA YANG DIPAKAI PENDUDUK BOGOR - Dina Handayani; Nunik Sri Ariyanti (Floribunda, 2015)
Torch ginger (Etlingera spp., Zingiberaceae) has long been known in Bogor as herbs and spices, however it has not been widely used as ornamental plants and cut flowers. An exploration was conducted to characterize the morphological variations and characteristics of vegetative before flowering. Two species of torch ginger (E. elatior and E. hemisphaerica) in Bogor and their flowers variation can be identified vegetatively by the characteristic of sheath (patterns of stripes, dots decoration, wax layer), and leaf bud (color). The inflorescence characters of E. elatior and E. hemisphaerica can be predicted based on the colour of sheath and scales of rhizomes.